Neuroprotective effect of Astragali Radix on cerebral infarction based on proteomics - Li, Ying; Wang, Daoping; Guo, Rongjuan; Ma, Bo; Miao, Lan; Sun, Mingqian; He, Lijuan; Lin, Li; Pan, Yinghong; Ren, Junguo; Liu, Jianxun (Frontiers in Pharmacology, 2023)
Objective: Astragali Radix (AR, Huangqi in Chinese) has a neuroprotective effect on cerebral infarction (CI). In order to explore the biological basis and therapeutic mechanism of AR in CI, a double-blind randomized controlled trial was established in this study, and proteomics analysis was carried out on serum samples of patients. Methods: The patients were divided into the AR group (n=35) and the control group (n=30). The curative effect was evaluated by TCM syndrome score and clinical indicators, and the serum of the two groups was analyzed by proteomics. Based on bioinformatics analysis methods, explore the changes in differential proteins between two groups of samples, and the key proteins were validated through enzyme-linked immunosorbent assay (Elisa). Results: The results of this study showed that the scores of Deficiency of Vital Energy (DVE), Blood Stasis (BS) and NIHSS decreased significantly (p<0.05), while the scores of Barthel index (BI) increased, indicating that AR could significantly improve the symptoms of CI patients. In addition, we found that compared with the control group, AR up regulated 43 proteins and down regulated 20 proteins, mainly focusing on anti atherosclerosis and neuroprotective effects. Moreover, Elisa indicated the level of IL-6, TNF-α, VCAM-1, MCP-1 and ICAM-1 were significantly decreased in the serum of the AR group (p<0.05, p<0.01). Conclusion: This study found that AR can significantly recovery the clinical symptoms of CI. Serum proteomics research results show that AR may act on IL-6, TNF-α, VCAM-1, MCP-1 and ICAM-1, and play an anti atherosclerosis and neuroprotective role.